A produção da atividade pesqueira extrativista do estado do Amazonas no período de 2013 a 2023 - Frutuoso, Narcos Vinicius Ribeiro (Brasil, 2025)
This study aimed to analyze the productive profile of artisanal and managed fisheries in the state of Amazonas, as well as to describe the contribution of each microregion to the state’s total production from 2013 to 2023. To achieve this, the following specific objectives were outlined: a) to present the productive performance of artisanal and managed fisheries, considering the number of fishermen and large vessels in each microregion; b) to describe the main productive species in different microregions; and c) to characterize the productive profile of artisanal and managed fisheries. This descriptive research utilized secondary data, mainly collected through Institute of Agricultural and Sustainable Forestry Development of the State of Amazonas. The results indicated that, although managed fishing is growing, the extractive fishing production in Amazonas is still dominated by artisanal fishing. The microregions of Rio Negro/Solimões, Purus, and Jutaí/Solimões/Juruá concentrate the majority of artisanal fishing production. In terms of managed fishing, the Rio Negro/Solimões and Alto Solimões microregions stand out. The Rio Negro/Solimões microregion has the largest number of artisanal fishermen, while Jutaí/Solimões/Juruá has the highest number of managed fishing practitioners. Additionally, Rio Negro/Solimões registered the highest number of artisanal fishing vessels across all years. Jaraqui is the most fished, traded, and consumed fish in Amazonas. The number of artisanal fishermen, managed production, and per capita income are key variables influencing artisanal fishing production, while the number of fishermen in both fishing modalities is the only variable influencing managed fishing production.